KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS IX SMP PGRI 2 PEKANBARU - Sari, Suci Pebrian; Razak, Abdul; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absrtact: This research aimed to find out the level of ability to write short stories of clas X F students of SMP PGRI 2 Pekanbaru, and to know whether or not there is a difference in writing short stories between male and female students of class X F students of SMP PGRI 2 Pekanbaru. Writing short stories is the ability to express thoughts and feelings into written form of fiction and nonfiction (short story) which contains elements of themes, characters, plot, setting, point of view, style of language and massages that is conveyed to the reader, which is presented in an interesting and suggestive language. The method used in this research is quantitative descriptive method. The data source used was the score of the ability to write short stories of class IX student of SMP PGRI 2 Pekanbaru. The test was conducted by using a nonparametic test, ad using the Mann Whitney test. Based on the test results, it was concluded that the ability to write short stories of class IX F student of SMP PGRI 2 Pekanbaru was classified as moderate and there was no difference in the ability to write short stories between male and female students of class IX Fstudents of SMP PGRI 2 Pekanbaru.Key Words: Short stories, writing skill